N-Methyl-D-Aspartate Receptor Link to the MAP Kinase Pathway in Cortical and Hippocampal Neurons and Microglia Is Dependent on Calcium Sensors and Is Blocked by α-Synuclein, Tau, and Phospho-Tau in Non-transgenic and Transgenic APPSw,Ind Mice - Franco, Rafael; Aguinaga, David; Reyes, Irene; Canela, Enric I.; Lillo, Jaume; Tarutani, Airi; Hasegawa, Masato; del Ser-Badia, Anna; del Rio, José A.; Kreutz, Michael R.; Saura, Carlos A.; Navarro, Gemma (Frontiers in Molecular Neuroscience, 2018)
N-methyl-D-aspartate receptors (NMDAR) respond to glutamate to allow the influx of calcium ions and the signaling to the mitogen-activated protein kinase (MAPK) cascade. Both MAPK- and Ca2+-mediated events are important for both neurotransmission and neural cell function and fate. Using a heterologous expression system, we demonstrate that NMDAR may interact with the EF-hand calcium binding proteins calmodulin, calneuron-1 and NCS1 but not with caldendrin. NMDAR were present in primary cultures of both neurons an microglia from cortex and hippocampus. Calmodulin in microglia, and calmodulin and NCS1 in neurons, are necessary for NMDA-induced MAP kinase pathway activation. Remarkably, signaling to the MAP kinase pathway was blunted in primary cultures of cortical and hippocampal neurons and microglia from wild type animals by proteins involved in neurodegenerative diseases: α-synuclein, Tau and p-Tau. A similar blockade by pathogenic proteins was found using samples from the APPSw,Ind transgenic Alzheimer’s disease model. Interestingly, a very marked increase in NMDAR-NCS1 complexes was identified in neurons and a marked increase of both NMDAR-NCS1 and NMDAR-CaM complexes was identified in microglia from the transgenic mice. The results show that α-synuclein, Tau and p-Tau disrupt the signaling of NMDAR to the MAPK pathway and that calcium sensors are important for NMDAR function both in neurons and microglia. Finally, it should be noted that the expression of receptor-calcium sensor complexes, specially those involving NCS1, is altered in neural cells from APPSw,Ind mice embryos/pups.